Structural Alteration, Hydration Stability, Heavy Metal Removal Efficiency, and Montmorillonite Porosity Fate by Coupling the Soil Solution pH and a Thermal Gradient - Chadha Mejri; Walid Oueslati; Abdesslem Ben Haj Amara (Adsorption Science & Technology)
Clay minerals are considered as a promising material in the context of geological barrier for the confinement of radioactive and industrial waste. Understanding the usefulness of the smectite mineral, in this approach, remains insufficient. The deep investigation about structural response/changes, hydrate stability, cation exchange process, permeability, and heavy metal/radionuclide adsorption/removal efficiency under external constraints is needed. To explore the structural alteration, the hydration stability, and the evolution of montmorillonite porosity under a first order of external applied constraints coupling, a reference Na-rich montmorillonite specimen is used as a starting material, and three exchangeable heavy metal cations (Ba2+, Cu2+, and Co2+) have been selected. The applied constraint coupling is realized at laboratory scale and assured by simultaneously varying of the soil solution pH and the thermal gradient. The evaluation of the mineral fraction response is established by correlation of quantitative XRD analysis results, thermal analysis, and porosity measurements. The quantitative XRD analysis allows rebuilding of the theoretical model describing the interlamellar space (IS) configurations/damages, structural heterogeneity degrees, and hydrous stability. Obtained results show a dominant interstratified hydration character, for all studied complexes, attributed to a new IS organization versus the applied constraint strength. Furthermore, all samples exhibit a heterogeneous hydration behavior traduced by the coexistence of different layers of type population within the crystallite. Additionally, the theoretical XRD profile decomposition allowed us to prove link between the domination of the segregated stacking layers mode against the constraint strength. Thermal analysis allowed us to develop theoretical models describing the decrease of the water molecule amounts as a function of the increase in temperature and soil solution pH. Moreover, a specific hydration footprint response and an interstratification mapping are assigned for each corresponding stress degrees. The evolution of montmorillonite porosity is determined by adsorption measurement, based on Brunauer, Emmett, and Teller (BET) and Barrett-Joyner-Halenda (BJH) pore size distribution analyses which confirms for all samples, the exfoliation process, and the mesopore diameter rise by increasing the constraint intensity.